Extraordinary role of resonant dopant vanadium for improving thermoelectrics in n-type PbTe. (January 2023) - Zhong, Yan; Lv, Fangling; Zhao, Xuanwei; Deng, Qian; An, Xiang; He, Zhengmin; Gan, Lin; Ang, Ran
Abstract: Inspired by the bottleneck that the optimization of the dimensionless figure of merit zT is limited by the concept of amorphous limit, impurity-induced band structure distortion independent of phonon properties opens up an effective avenue to significantly enhance room-temperature thermoelectrics of narrow-bandgap materials. In this work, density functional theory calculations confirm the virtual bound state of vanadium at the bottom of the conduction band in n -type PbTe. The effectiveness of the resonant level in enhancing electrical properties not only depends on the electronic structure or scattering mechanism near the chemical potential, but also on the Fermi level. Therefore, a delicate manipulation of the Fermi level is achieved by trace copper substitution to optimize the thermoelectric performance. Furthermore, based on the single parabolic band model and the relaxation time approximation, the dominant term of the transition-metal localized d -electron resonant state in increasing the Seebeck coefficient is clarified in n -type PbTe, which is significantly different from that of the thallium resonant level. More importantly, combined with the mechanism of shortening phonon relaxation time through multi-scale defect sources, the lattice thermal conductivity is drastically reduced. Here, the n -type Pb0.967 Cu0.003 V0.03 Te sample enables an increased peak zT of ∼1.3, as well as the average zT avg of ∼1.1 from 523 to 823 K. The current findings provide a paradigm for the transition-metal resonant states to regulate thermoelectrics. Graphical abstract: Transition-metal resonant states with Fermi level manipulation optimize the near-room-temperature zT of n -type PbTe. Image 1 Highlights: Density functional theory confirms the virtual bound state of vanadium in n -type PbTe. The dominant term of the localized d -electron resonant state in increasing Seebeck coefficient is clarified. Manipulate the Fermi level for optimizing peak zT ∼1.3, as well as the average zT avg ∼1.1 from 523 to 823 K.